Lemon Juice as a Biocatalyst Under Ultrasound Irradiation: Synthesis and Pharmacological Evaluation of 2-amino 1,3,4-thiadiazoles - Prasad, Malavattu G.; Lakshmi, Chapala V.; Katari, Naresh K.; Pal, Manojit (Anti-Cancer Agents in Medicinal Chemistry, 2020)
Background: The 2-amino 1,3,4-thiadiazole framework has attracted considerable interest because of its prevalence in compounds possessing a wide range of pharmacological properties including anticancer/antitumor activities. Though a number of methods have been reported for the synthesis of this class of compounds, some of them are not straightforward, inexpensive and environmentally friendly. Objective: To synthesize 2-amino-1,3,4-thiadiazole derivatives that could act as potential anticancer agents. Methods: The use of lemon juice as an inexpensive and readily available biocatalyst was explored in the synthesis of 2-amino 1,3,4-thiadiazole derivatives. Accordingly, a convenient method has been developed for the rapid synthesis of this class of compounds under a mild and non-hazardous reaction condition in good yields. The methodology involved the reaction of various acid hydrazides with TMSNCS in the presence of lemon juice in PEG-400 at room temperature (25-30°C) under ultrasound irradiation. These compounds were assessed for their cytotoxic properties against two different metastatic breast cancer cell lines e.g., MDAMB-231 and MCF-7 and subsequently against SIRT1. Results: The 2-amino 1,3,4-thiadiazole derivatives 3a, 3i, 3j and 3l showed promising growth inhibition of MDAMB- 231 and MCF-7 cell lines and SIRT1 inhibition in vitro. Indeed, 3i was found to be a potent inhibitor of SIRT1. Conclusion: An ultrasound-assisted method facilitated by lemon juice has been developed to synthesize 2-amino- 1,3,4-thiadiazole derivatives that could act as potential anticancer agents.
Keywords: PEG-400